The future of education and ICT (Journal of Parents and Teachers, 2013)
ICT have become in the last century and even more in the XXI century as a source of information and management of it , but also it is a resource for teaching and learning. We can detail them in three dimensions: learning about ICT , learning ICT and learning with ICT. Through them, we see the enormous functionality of these resources to promote the integral development of every human being .
Keywords: Project work; interdisciplinary; creative learning; cooperative learning; educational technology; film and education; values ​​education